The Evolution of Fahombo: Analyzing Its Changing Significance in the Context of Cultural Dynamics and Modernization - Gulo, Merlin Soviana; Munthe, Samantha Mariani; Mendrofa, Novi Oktavia; Sihombing, Noel; Arianto, Tomi (Yayasan Tri Edukasi Ilmiah, 2024)
This study aims to analyze the shift in the meaning of Fahombo in the dynamics of culture and modernization using the theory of diffusion of innovation from Everett Rogers (1962). This theory highlights how changes in Nias culture occur through the process of innovation, communication, time, and social systems. In this context, Fahombo is not only maintained as a cultural heritage, but also experiences adaptation due to the influence of modernization and globalization. This study uses a descriptive qualitative approach with a virtual interview method via the Zoom application to explore in depth the information needed. The informants involved consisted of parents who had experienced or witnessed Fahombo in a traditional context, community leaders who had a deep understanding of the history and changes in the tradition, and local residents who witnessed firsthand the transformation of Fahombo in recent decades. The results of the study show that the shift in the meaning of Fahombo occurs through five stages of innovation adoption according to Rogers, namely: awareness, interest, evaluation, experimentation, and acceptance. Traditional values are maintained, but reinterpretation occurs in the context of tourism, cultural identity, and social expression. This transformation reflects the process of social and selective adaptation in which local and global elements interact to form a new understanding of Fahombo in contemporary Nias society. This study provides insights into how traditions can survive and thrive in changing social systems.